Regional collaboration in the Middle East to deal with H5N1 avian flu. Issue 7573 (19th October 2006) - Leventhal, Alex; Ramlawi, Assad; Belbiesi, Adel; Balicer, Ran D
Abstract : In 2005-6 Arab and Israeli collaboration contained outbreaks of avian flu in the Middle East. This initiative shows how building relationships through joint efforts creates an infrastructure for cross border collaboration during emergencies